The Antibiotic Resistance Profiles of Bacterial Strains Isolated from Patients with Hospital-Acquired Bloodstream and Urinary Tract Infections - Hamed Ghadiri; Hamid Vaez; Samira Khosravi; Ebrahim Soleymani (Critical Care Research and Practice)
Treatment of nosocomial infections is becoming difficult due to the increasing trend of antibiotics resistance. Current knowledge on antibiotic resistance pattern is essential for appropriate therapy. We aimed to evaluate antibiotic resistance profiles in nosocomial bloodstream and urinary tract pathogens. A total of 129 blood stream and 300 urinary tract positive samples were obtained from patients referring to Besat hospital over a two-year period (2009 and 2010). Antibiotic sensitivity was ascertained using the Kirby-Bauer disk diffusion technique according to CLSI guidelines. Patient's data such as gender and age were recorded. The ratio of gram-negative to gram-positive bacteria in BSIs was 1.6 : 1. The most prevalent BSI pathogen was Coagulase-Negative Staphylococci (CoNS). The highest resistance rate of CoNS was against penicillin (91.1%) followed by ampicillin (75.6%), and the lowest rate was against vancomycin (4.4%). Escherichia coli was the most prevalent pathogen isolated from urinary tract infections (UTIs). Ratio of gram-negative to gram-positive bacteria was 3.2 : 1. The highest resistance rate of E. coli isolates was against nalidixic acid (57.7%). The present study showed that CoNS and E. coli are the most common causative agents of nosocomial BSIs and UTIs, and control of infection needs to be addressed in both antibiotic prescription and general hygiene.